2007
DOI: 10.1002/bem.20385
|View full text |Cite
|
Sign up to set email alerts
|

Indoor transformer stations as predictors of residential ELF magnetic field exposure

Abstract: Transformer stations in apartment buildings may offer a possibility to conduct epidemiological studies that involve high exposure to extremely low frequency magnetic fields (MF), avoid selection bias and minimize confounding factors. To validate exposure assessment based on transformer stations, measurements were performed in thirty buildings in three Finnish cities. In each building, spot measurements in all rooms and a 24-h recording in a bedroom were performed in one apartment above a transformer station (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 11 publications
6
28
0
Order By: Relevance
“…Because the location of an apartment relative to the ITS can easily be identified, this approach can reliably be used for exposure assessment in an epidemiologic study without obtaining access to the residences. Overall, the results of our study are in good agreement with those reported by Ilonen et al (2008) and Thuro´czy et al (2008). Dissimilarities in the MF exposure among different countries should be considered in any future research and emphasis should be given to the necessity of a comprehensive technical characterization of the ITSs before conducting any exposure assessment study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Because the location of an apartment relative to the ITS can easily be identified, this approach can reliably be used for exposure assessment in an epidemiologic study without obtaining access to the residences. Overall, the results of our study are in good agreement with those reported by Ilonen et al (2008) and Thuro´czy et al (2008). Dissimilarities in the MF exposure among different countries should be considered in any future research and emphasis should be given to the necessity of a comprehensive technical characterization of the ITSs before conducting any exposure assessment study.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, they can be used as a control group due to similar socioeconomic status (SES) of the population of those floors (the SES in Israel is generally related to the floor level of the apartment). These results are similar to those reported by Thuro´czy et al (2008), but differ from those of Ilonen et al (2008), where MFs of FF are higher than those of the HF.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Conducted measurements for the pilot TRANSEXPO study, show a clear distinction between the magnetic field values in the "exposed" apartments and all other apartments located on same buildings [6,7,8]. The apartments located on the same floor as the "exposed" ones can not be considered as an"unexposed", taking into account the measured values of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…The concerns over the possible biological effects of power lines and other power sources began in 1979, when Wertheimer and Leeper reported that children living in the vicinity of high-voltage transmission lines have a higher risk of developing leukemia. Although a number of researches have been conducted on this subject, the biological effects of EMF remain a heated technological and medical controversy [2][3][4][5][6][7][8][9][10][11][12]. An indirect method to estimate the MF exposure level of the children, who were less than 17 years of age, was developed in this study.…”
Section: Introductionmentioning
confidence: 99%